Reliability, Validity, and Responsiveness of the Chinese Learning Accomplishment Profile (C-LAP) - Deng Chen (MDPI AG, 2021)
Objectives: To evaluate the reliability, validity, and responsiveness of the Chinese Learning Accomplishment Profile in China. Methods: 12,098 participants aged from 0 to 36 months from 30 provinces (mostly from Shanghai) in China were enrolled between 2013 and 2020. The reliability was reflected by Pearson correlation coefficients, Cronbach’s alpha coefficients and standard errors; the validity was shown by the coefficients between the dimensions, and we also evaluated the responsiveness as a supplement to the validity. Results: Reliability: in six domains among each subgroup, Pearson correlation coefficients between developmental age and chronological age ranged from 0.89 to 0.98, Cronbach’s alpha coefficients from 0.71 to 0.99, and standard errors from 0.15 to 2.76. Validity: after controlling for chronological age, the correlation coefficients between the dimensions were between 0.18 and 0.78, and most of them were below 0.70. Responsiveness: developmental age of all domains obtained via the Chinese Learning Accomplishment Profile system changed significantly (p < 0.001) with time (gap of 1–3 months), and the standardized response mean ranged from 0.66 to 2.45. Conclusions: The Chinese Learning Accomplishment Profile is suitable for assessing children’s development in Shanghai, but still needs confirmation when used in other provinces in China due to the great differences between regions in China.